Stručná historie a současnost průtokové injekční analýzy a kapilární elektroforézy v České republice - Chocholouš, Petr; Polášek, Miroslav; Kubáň, Petr; Foret, František (Chemické listy, 2021)
This article describes the history, development, and current state of two analytical methods to which Czech scientists have made significant contributions. It describes the first steps of these methods in Czechoslovakia during the 1970s and 1980s, the development of the methods through innovation, and the establishment of cooperation with foreign scientists. Today, Czech scientists from the Department of Analytical Chemistry, Faculty of Pharmacy in Hradec Králové, Charles University, and Institute of Analytical Chemistry of the Czech Academy of Sciences in Brno are among the major contributors to these fields of analytical chemistry. The milestones in the development and the prominent scientists mentioned in the individual chapters give a chance for a bright future for these methods, not only in the Czech Republic.
Keywords: Česká republika; History, 21st Century; průtoková injekční analýza; Czech Republic; Electrophoresis, Capillary; dějiny 20. století; lidé; elektroforéza kapilární; History, 20th Century; Humans; dějiny 21. století; Flow Injection Analysis